Uso de aditivos na biodegradação de madeira pelo fungo Ceriporiopsis subvermispora: efeito na peroxidação de lipídios dependente de manganês-peroxidase - Aguiar,André (2012)
Ceriporiopsis subvermispora is a selective fungus in the wood delignification and the most promising in biopulping. Through the lipid peroxidation initiated by manganese peroxidase (MnP), free radicals can be generated, which can act in the degradation of lignin nonphenolic structures. This work evaluated the prooxidant activity (based in lipid peroxidation) of enzymatic extracts from wood biodegradation by this fungus in cultures containing exogenous calcium, oxalic acid or soybean oil. It was observed that MnP significant activity is required to promote lipid peroxidation and wood delignification. Positive correlation between prooxidant activity x MnP was observed up to 300 IU kg-1 of wood.